Relationship between Moral Distress and Job Satisfaction among Nurses of Tehran University of Medical Sciences Hospitals - Hamid Haghani; Fatemeh Hajibabaee; Forough Rafii; Hamid Reza Jalili; Soodabeh Joolaee (Tehran University of Medical Sciences, 2012)
Background & Aim: Moral distress, a major issue in nursing, affects nurses in all healthcare sections. The existence of such distress and its consequent job dissatisfaction may pose a threat to nurses' physical and mental health, as well as their quality of life; and hinder their accomplishment of individual and social goals. The aim of this study was to determine the relationship between the moral distress and job satisfaction In nurses. Methods & Materials: This cross-sectional correlational study was conducted on 210 nurses employed in the selected healthcare centers of Tehran University of Medical Sciences in 2009. Data were collected using a questionnaire consisting demographic characteristics, the Corley's moral distress scale, and the Minnesota Satisfaction Questionnaire. Data were analyzed using descriptive statistics and independent t-test, analysis of variance, Wilcoxon test and Pearson's correlation coefficient in the SPSS v.14. Results: According to the findings of the study, the mean of the moral distress was 1.77 out of four; and the mean of the job satisfaction score was 3.17 out of 5; indicating a moderate job satisfaction among the nurses. A significant relationship was observed between the moral distress and nurses' job satisfaction in the present study, indicating that by decreasing moral distress, job satisfaction increases. Conclusion: Although numerous factors govern nurses' job satisfaction, the observed relationship between moral distress and job satisfaction indicates that identifying and limiting factors influencing these distresses can lead to improved job satisfaction for nurses.